EDIBLE FILM CHARACTERISTICS WITH CARRAGEENAN (Eucheuma cottonii) FLOUR EXTRACTED WITH DIFFERENT BASE SOLVENTS - Sirait, Putriana Sari; Diharmi, Andarini; Azmi, Heriza (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Riau, 2025)
Edible film is a primary packaging in the form of a thin layer and functions as a coating for food ingredients, which can be made from hydrocolloid compounds. Carrageenan polysaccharide is one of the hydrocolloids used to make edible films because it produces strong gel properties. Eucheuma cottonii is a seaweed that produces relatively high levels of kappa carrageenan, namely around 50%. This research aims to determine the physical and mechanical characteristics of edible film with carrageenan flour from E. cottonii extracted with different base solvents. The research method was carried out experimentally with an experimental design, namely a non-factorial Completely Randomized Design (CRD) with three levels of treatment, namely differences in carrageenan flour extracted with KOH, NaOH and Ca(OH)2 solvents. The parameters of this research are physical and mechanical analysis of edible film including testing tensile strength, thickness, percent elongation, and water vapor transmission rate. The research results showed that the best results were in the treatment of carrageenan flour extracted with KOH solvent, where the physical and mechanical analysis of the edible film showed a tensile strength value of 9.49±0.50 MPa, a thickness of 0.03±0.003 mm, a water vapor transmission rate of 30.13±0.41 g/m2/day, and a percent elongation 9.86±0.41%.